Synthetic Approaches for the Construction of Five- and Six-Membered Silaazacycles - Wang, Wanshu; Gao, Lu; Song, Zhenlei (Synthesis, 2022)
Silaazacycles (or azasilacycles), containing both nitrogen and silicon atoms, are appealing ring structures in the development of silicon-containing functional molecules. The development of general and efficient methods towards these motifs has therefore attracted considerable attention from synthetic chemists. This short review intends to highlight representative advances in the synthesis of five- and six-membered silaazacycles.1 Introduction2 Five-Membered Silaazacycles2.1 Five-Membered Silaazacycles bearing a 1,2-N/Si Moiety2.2 Five-Membered Silaazacycles bearing a 1,3-N/Si Moiety3 Six-Membered Silaazacycles3.1 Six-Membered Silaazacycles bearing a 1,2-N/Si Moiety3.2 Six-Membered Silaazacycles bearing a 1,3-N/Si Moiety3.3 Six-Membered Silaazacycles bearing a 1,4-N/Si Moiety4 Conclusion
Keywords: silaazacycles; azasilacycles; cyclization; ring expansion; carbon-silicon switching; N-substitution